The Relationship Between Physical Activity In Physical Education And Student Academic Achievement - Afrizal, Agus; Karo Karo, Alan Alfiansyah Putra; Sari, Liliana Puspa (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
This study aims to investigate the correlation between physical activity in the context of physical education and students' academic performance. The methodological framework used is a quantitative correlational and cross-sectional design. The study was conducted from April 15 to May 15, 2025, involving 187 participants from elementary, middle, and high schools spread across six educational institutions in North Sumatra. The sampling methodology employed purposive sampling, targeting students actively engaged in physical education (PJOK) and willing to complete an online questionnaire. The study utilized a questionnaire derived from the Global Physical Activity Questionnaire (GPAQ). This instrument assesses the prevalence and duration of physical activity, sedentary behavior, and students' perceptions of the importance of physical activity. Students' academic performance was measured using the average scores from their final semester reports. Data analysis was conducted using descriptive statistics alongside Pearson's correlation test. The study findings revealed a Sig. (2-tailed) value of 0.001, which is less than the 0.05 threshold, indicating a statistically significant correlation between the Physical Activity (X) and Academic Performance (Y) variables. These results suggest that consistent engagement in physical activity has the potential to enhance cognitive function and promote academic success among students. Consequently, the integration of physical activity plays a crucial role in promoting the holistic development of students' academic abilities and overall health.